2014
DOI: 10.1242/bio.20146130
|View full text |Cite
|
Sign up to set email alerts
|

Drag, but not buoyancy, affects swim speed in captive Steller sea lions

Abstract: Swimming at an optimal speed is critical for breath-hold divers seeking to maximize the time they can spend foraging underwater. Theoretical studies have predicted that the optimal swim speed for an animal while transiting to and from depth is independent of buoyancy, but is dependent on drag and metabolic rate. However, this prediction has never been experimentally tested. Our study assessed the effects of buoyancy and drag on the swim speed of three captive Steller sea lions (Eumetopias jubatus) that made 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…As far as buoyant lift is concerned, it is mainly linked with the criterion of good performance for an animal that takes into account that how much energy it can process and store (guts, so to speak) and how many offspring it can produce (gonads, loosely put). In the case of Sealion, the maximum available buoyant lift is 50% of the gross weight (Suzuki et al, 2014). This digit is consistent with the recent findings related to the optimum buoyancy ratio for hybrid airship (Raymer, 2006).…”
Section: Buoyant Liftsupporting
confidence: 91%
See 3 more Smart Citations
“…As far as buoyant lift is concerned, it is mainly linked with the criterion of good performance for an animal that takes into account that how much energy it can process and store (guts, so to speak) and how many offspring it can produce (gonads, loosely put). In the case of Sealion, the maximum available buoyant lift is 50% of the gross weight (Suzuki et al, 2014). This digit is consistent with the recent findings related to the optimum buoyancy ratio for hybrid airship (Raymer, 2006).…”
Section: Buoyant Liftsupporting
confidence: 91%
“…Interestingly, as per the findings of Suzuki et al (2014) this range of fineness ratio is found comparable to the California sea lion. This marine animal has a fineness ratio of 5.55 and location of maximum thickness of outer profile is at 34% of the overall length (Cheneval, 2005).…”
Section: Optimum Fineness Ratiosupporting
confidence: 85%
See 2 more Smart Citations
“…Drag harnesses (Cornick et al, 2006), collars (Lang and Daybell, 1963), pipes (Aoki et al, 2011;Suzuki et al, 2014), wooden blocks (Boyd et al, 1997) have been attached to marine mammals while measuring their long-term energy consumption with radio-isotope labeled water (Costa and Gentry, 1986), heat flux (Willis et al, 2005) their diving and swimming behaviors (Boyd et al, 1997;Aoki et al, 2011), or their colony return rates (Costa and Gentry, 1986;Boyd et al, 1997).…”
Section: Changes In Force Balancementioning
confidence: 99%